Enhancing effects of anti-CD40 treatment on the immune response of SCID-bovine mice to Trypanosoma congolense infection - Haas, K.M.; Taylor, K.A.; MacHugh, Niall D.; Kreeger, J.M.; Estes, D.M. (Oxford University Press, 2001)
African trypansosomes are tsetse-transmitted parasites of chief importance in causing disease in livestock in regions of sub-Saharan Africa. Previous studies have demonstrated that certain breeds of cattle are relatively resistant to infection with trypanosomes, and others are more susceptible. Because of its extracellular location, the humoral branch of the immune system dominates the response against Trypanosoma congolense. In the following study, we describe the humoral immune response generated against T. congolense in SCID mice reconstituted with a bovine immune system (SCID-bo). SCID-bo mice infected with T. congolense were treated with an agonistic anti-CD40 antibody and monitored for the development of parasitemia and survival. Anti-CD40 antibody administration resulted in enhanced survival compared with mice receiving the isotype control. In addition, we demonstrate that the majority of bovine IgM+ B cells in SCID-bo mice expresses CD5, consistent with a neonatal phenotype. It is interesting that the percentage of bovine CD5+ B cells in the peripheral blood of infected SCID-bo mice was increased following anti-CD40 treatment. Immunohistochemical staining also indicated increased numbers of Ig+ cells in the spleens of anti-CD40-treated mice. Consistent with previous studies demonstrating high IL-10 production during high parasitemia levels in mice and cattle, abundant IL-10 mRNA message was detected in the spleens and peripheral blood of T. congolense-infected SCID-bo mice during periods of high parasitemia. In addition, although detected in plasma when parasites were absent or low in number, bovine antibody was undetectable during high parasitemia. However, Berenil treatment allowed for the detection of VSG-specific IgG 14 days postinfection in T. congolense-infected SCID-bo mice. Overall, the data indicate that survival of trypanosome-infected SCID-bo mice is prolonged when an agonistic antibody against bovine CD40 (ILA156) is administered. Thus, stimulation of B cells and/or other cell types through CD40 afforded SCID-bo mice a slight degree of protection during T. congolense infection.